Hyperventilation in Panic Disorder and Asthma: Empirical Evidence and Clinical Strategies - Meuret, Alicia E. (2010)
Sustained or spontaneous hyperventilation has been associated with a variety of physical symptoms and has been linked to a number of organic illnesses and mental disorders. Theories of panic disorder hold that hyperventilation either produces feared symptoms of hypocapnia or protects against feared suffocation symptoms of hypercapnia. Although the evidence for both theories is inconclusive, findings from observational, experimental, and therapeutic studies suggest an important role of low carbon dioxide (CO(2)) levels in this disorder. Similarly, hypocapnia and associated hyperpnia are linked to bronchoconstriction, symptom exacerbation, and lower quality of life in patients with asthma. Raising CO(2) levels by means of therapeutic capnometry has proven beneficial effects in both disorders, and the reversing of hyperventilation has emerged as a potent mediator for reductions in panic symptom severity and treatment success.